Wyznaczanie Energii Dostarczonej do Elektrycznej Rurki Uderzeniowej - Mucha, Z.; Pietrzyk, Z.A. (Engineering Transactions, 1966)
The present paper describes a method for determining the energy input in an electric shock tube based on the relations, obtained experimentally, between the intensity of current and the time in the discharge circuit including a shock tube or if the electrodes are short-circuited. The character the diagram of the energy furnished to the shock tube with an axial electrode, filled up with nitro-gen, in function of the initial energy of the condensers approaches that of the velocity diagram of the shock wave in function of the same argument. This fact explains to some extent the accurrenceof maximum wave velocity observed in Refs. [1 and 2].